TEKNIK MEMBACA NYARING TERHADAP KEMAMPUAN MENYIMAK DONGENGS SISWA SEKOLAH DASAR: STUDI KEPUSTAKAAN - Ardi Yanto; Risma Nuriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Listening skill is one of the essential foundations of literacy learning in elementary school. However, students often encounter difficulties in maintaining concentration, understanding story content, and identifying moral messages. This study aims to examine the effect of the read aloud technique on elementary school students’ listening skills in fairy tale learning through a literature review approach. Data were collected from relevant scientific literature published between 2021 and 2025 and analyzed using the interactive model of Miles and Huberman. The findings show that the read aloud technique contributes significantly to students’ listening skills in cognitive, linguistic, and affective aspects. Cognitively, it helps improve memory retention and story comprehension through appropriate intonation. Linguistically, it enriches students’ vocabulary through story context. Affectively, it creates an enjoyable learning atmosphere that increases student attention and engagement. Therefore, read aloud is an effective instructional strategy for improving elementary students’ listening skills in fairy tale learning.